Sartre - "Levy, Neil" (Oxford, 2007)
This introduction traces the philosophical achievements of a thinker so influential that his death in 1980 brought 50,000 people on to the streets of Paris. The account of Jean-Paul Sartre - writer, journalist and intellectual cornerstone of the 20th century - stretches from his early existential phase to his later Marxist beliefs. With coverage of such major contemporary issues as human liberty, sociobiology, the ethics of work, and the influence of genetics on ideas of individual freedom, Neil Levy uses a range of original material not only to introduce Sartre and his work, but also to highlight his continuing relevance to today's moral and scientific climate. At the heart of this study is a focus on the ethical dimension of Jean-Paul Sartre's philosophical thought: a focus which challenges us to consider more closely the shape of our lives, and the manner in which human beings should treat one another.
Keywords: Philosophers